Understanding Captcha: with its types,for security (International Journal of Engineering and Computer Science, 2016)
CAPTCHAs are short for Completely Automated Public Turing test to tell Computer and Humans Apart.This test is taken to insure that the user is a human being and not the machine or any program.It contains different types of tests which can only be solved by the humans.this is because to avoid bad interface of machines in an application. Captcha as graphical passwords (CaRP) is one of the new security built on Captcha technology. As its name implies that CaRP is the combination of both CAPTCHA and Graphical password scheme. CaRP addresses a number of security problems altogether, it offers reasonable security and usability with some practical applications for improving online security